Charge Transport of Silicon(Iv) and Zinc(Ii) Phthalocyanines by Molecular Junction Models - Cardenas-Jiron, G; Zambrano-Angulo, M (Royal Society of Chemistry, 2024)
In this work, we present a theoretical study on the electronic and charge transport properties of substituted silicon (SiPc) and zinc (ZnPc) phthalocyanines, focusing on their potential utility in solar cells. The effect of various substituents (hydroxyl and primary and secondary amines), central atoms (Zn and Si), and anchor groups (anhydrous and carboxyl) on these properties was systematically analyzed. The band gap energy (Eg) of phthalocyanine-TiO2 was calculated using the band structure for periodic systems with density functional theory (DFT) calculations, employing the meta-GGA and hybrid exchange–correlation functionals. The TB09LDA functional predicted the band gap and density of states (DOS) better. Eg for TiO2 (3.2 eV) decreased in a significative form for the phthalocyanines adsorbed on TiO2 with values in the range of 0.22–0.38 eV. The charge transport properties calculated through non-equilibrium Green’s functions combined with DFT (DFT-NEGF) results revealed a superior conductance in silicon-based systems, characterized by transmission peaks near the Fermi level, resulting in enhanced current values under applied voltage. Considering the substituents and anchor groups evaluated, it was found that silicon-based systems incorporating primary amines and carboxyl moieties exhibited the highest current values, reaching up to 0.23 mA. The results aligned with the desirable attributes required for potential solar cell applications, suggesting that silicon phthalocyanines can be good candidates in photovoltaics. © The Royal Society of Chemistry 2025.